2021
DOI: 10.3390/plants10071265
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity and Chemical Composition of Essential Oils against Pathogenic Microorganisms of Freshwater Fish

Abstract: Antimicrobials are widely applied in aquaculture for treatment of infectious diseases in fish. The increased antimicrobial resistance of fish pathogens to conventional antimicrobial treatment highlights the need for research on the antibacterial properties of natural products—in this case, essential oils (EOs). The aim of the present study was to detect the antimicrobial activity of the essential oils on pathogenic microorganisms found in freshwater fish. Freshwater fish isolates of Aerococcus spp., Aeromonas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…The tested oil can be almost considered as pure linalool. Regarding C. limon EO, the composition is quite similar to that reported by other authors [ 8 , 14 ], with its main component being α-limonene. In the scientific literature it has been reported that the major component of lemon EO is α-limonene, in the range of 51% [ 24 ] to 68% [ 21 ], together with other monoterpenes to complete the profile.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The tested oil can be almost considered as pure linalool. Regarding C. limon EO, the composition is quite similar to that reported by other authors [ 8 , 14 ], with its main component being α-limonene. In the scientific literature it has been reported that the major component of lemon EO is α-limonene, in the range of 51% [ 24 ] to 68% [ 21 ], together with other monoterpenes to complete the profile.…”
Section: Discussionsupporting
confidence: 87%
“…The composition of the EOs used in the present study showed high similarities with those of Klüga et al [ 8 ]. Few studies are available on C. camphora , and specifically on the chemotype Linaloolifera.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The products of medicinal plants like EOs and their antimicrobial properties have been empirically recognized for centuries, but recently the antimicrobial properties have been studied and confirmed scientifically [13][14][15]. These EOs effectively control the growth of different microorganisms like fungus, yeasts, bacteria, etc., which has been reported in several studies [16][17][18][19][20][21]. The bark extract of hog plums exhibits a valuable antibacterial activity, while the aqueous extract of the bark has shown a moderate antibacterial activity against Escherichia coli, Salmonella typhimurium, and Vibrio cholerae [22,23].…”
Section: Introductionmentioning
confidence: 69%